Carcinoid Tumor Development in an Intramedullary Spinal Cord Mature Teratoma - Fan, Xuemo; Turner, Jennifer E.; Turner, Thomas M.; Elrod, James P.; Clough, John A.; Howell, Everette I.; Johnson, Mahlon D. (American Journal of Neuroradiology, 2001)
Summary: The case of a 43-year-old woman with a several month history of severe back pain is reported. CT and MR imaging revealed an intramedullary cystic tumor, which was considered a dermoid cyst or teratoma. During surgery, the tumor was found within the base of the filum terminale and completely resected. Microscopic studies revealed a mature teratoma with an intramural carcinoid nodule. Thirteen-month follow-up after surgical resection showed no evidence of tumor recurrence or neoplasms elsewhere.